Sustainable development and international distribution: Theory and application to rainforests as carbon sinks - Ernst Mohr (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
A situation is analysed in which two countries negotiate the financing of the incremental costs which accrue if one of them switches from a non-sustainable onto a sustainable development path. The other country's incentive to pay arises as it benefits from the developing country's environmental resources, but at an ever declining rate as long as development remains non-sustainable. The paper shows that such negotiations generally induce a redistribution of welfare in favour of the developing country. This would hold even if both countries were identical except for the resource "ownership". Conditions are derived under which the developing country has an incentive to get on a "less" sustainable path in the pre-agreement phase. Furthermore, the analysis suggests the existence of a "window of history" implying that an agreement can only be reached in a subinterval of the resources' lifetime, if the window is open at all. In an application to the protection of tropical rainforests as carbon sinks it is shown that North to South redistribution of welfare would indeed be substantial, yet the North would still gain enormously in efficiency terms. An explanation is given why the Rio Conference failed in terms of rainforest protection.
Keywords: C72; F35; Q20; 330; Non-cooperative bargaining; environment; North-South cooperation; climate policy